Circular assembly of colloidal nanoparticles at the liquid–air interface mediated by block copolymers. Issue 23 (6th June 2018) - Wang, Lei; Yang, Yuchi; Shen, Xiudi; Li, Tongtao; Hu, Jianhua; Yang, Dong; Dong, Angang
Abstract : Ring-like nanoparticle superstructures can be achieved by block copolymer-mediated assembly at the liquid–air interface. Abstract : The self-assembly of colloidal nanoparticles (NPs) mediated by block copolymers (BCPs) is an efficient way for fabricating nanocomposite superstructures with precise geometric control. Here we report a generalized liquid–air interfacial strategy by exploiting the versatility in tuning the specific affinities between the grafted polymeric ligands and BCPs, enabling the circular assembly of NPs on a liquid surface to afford unique ring-like superstructures. Fe3 O4 NPs act as the model system; however, CoFe2 O4 and Au NPs are also demonstrated using the proposed assembly method. Functionalizing NPs with a specific polymeric ligand is the key to achieve the circular assembly of NPs, while both the subphase and the solvent annealing temperature have profound influence on the microphase separation behaviors of BCPs and therefore the morphology of the resulting NP assemblies. Moreover, the co-assembly of two types of NPs grafted with distinct polymeric ligands enables unprecendented heterogeneous concentric rings, with each ring consisting of one type of NP.